Specifics of Consumer Behavior in the Youth Segment of Kazakhstan Tourism - MUSSINA, Kamshat; MUTALIYEVA, Lyailya; BAIMBETOVA, Assel; SEIDUALIN, Darken; ABDRAMANOVA, Gulzhan; SHARAPAYEVA, Bota (Journal of Environmental Management and Tourism, 2020)
The article deals with the specifics of youth consumer behavior in tourism industry of the Republic of Kazakhstan. Consumer behavior of modern youth is one of the most important issues from the marketing point of view. Consumer behavior is a selection process that depends on values, tastes, habits, traditions, lifestyle, attitudes, etc. Consumer behavior processes are a type of complex system. Their intrinsic features include a large number of subprocesses, the influence of various factors on efficiency, the presence of subjects with different goal setting and motivation, the algorithm of the processes is not fixed. The market of youth tourism is accounted as one of the most important markets in tourism, as young travelers are at the very beginning of their tourism career, which in turn might potentially have impact on the future travel preferences and behavior. Though, the youth tourism market has a significant potential for increasing demand for travel and tourism, not much attention is paid to this tourism segment. In addition, tourists are identified in accordance with the concept of youth tourism by those who intend to travel for entertainment. This study helps explain the motivational factors of youth travelers and attempts to reveal the importance of the youth tourism market for specific tourist destinations.